2017
DOI: 10.2352/issn.2470-1173.2017.12.iqsp-225
|View full text |Cite
|
Sign up to set email alerts
|

Image Quality Assessment by Comparing CNN Features between Images

Abstract: Abstract.Finding an objective image quality metric that matches the subjective quality has always been a challenging task. We propose a new full reference image quality metric based on features extracted from Convolutional Neural Networks (CNNs). Using a pre-trained AlexNet model, we extract feature maps of the test and reference images at multiple layers, and compare their feature similarity at each layer. Such similarity scores are then pooled across layers to obtain an overall quality value. Experimental re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…The naïve approaches do this by simply computing mathematical distances between the images based on norms such as L 2 or L 1 , but these are well-known to be perceptually inaccurate [52]. Others have proposed metrics that try to exploit known aspects of the human visual system (HVS) such as contrast sensitivity [22], high-level structural acuity [52], and masking [48,51], or use other statistics/features [3,4,14,15,38,[44][45][46]53,54,57]. However, such hand-coded models are fundamentally limited by the difficulty of accurately modeling the complexity of the HVS and therefore do not work well in practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The naïve approaches do this by simply computing mathematical distances between the images based on norms such as L 2 or L 1 , but these are well-known to be perceptually inaccurate [52]. Others have proposed metrics that try to exploit known aspects of the human visual system (HVS) such as contrast sensitivity [22], high-level structural acuity [52], and masking [48,51], or use other statistics/features [3,4,14,15,38,[44][45][46]53,54,57]. However, such hand-coded models are fundamentally limited by the difficulty of accurately modeling the complexity of the HVS and therefore do not work well in practice.…”
Section: Introductionmentioning
confidence: 99%
“…compares our proposed dataset with the four largest existing IQA datasets 3. Our dataset is substantially bigger than all these existing IQA datasets combined in…”
mentioning
confidence: 99%
“…Other IQMs based on modelling the low-level vision have also been proposed, such the spatial CIELAB (S-CIELAB) [5]. In recent years the use of deep learning has attracted attention of many researchers [6,7,8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…22 naive human observers (10 men and 12 women, age [20][21][22][23][24][25][26][27], following the recommendation of minimum 15 observers by CIE [59] and ITU [60], were invited to give perceptual ratings to the different levels sharpness of images using a five force-choice based category judgment. The five categories, bad, poor, fair, good, and excellent, were represented by numbers from 1 to 5.…”
Section: Methodsmentioning
confidence: 99%
“…Gradient Magnitude Similarity Deviation (GMSD) [16] computes a local quality map by comparing the gradient magnitude maps of the reference and distorted image, and uses standard deviation to obtain the final IQ score. Amirshahi et al [26] proposed an IQ metric based on features extracted from Convolutional Neural Networks (CNNs), which produced good results on different databases. Zhao et al [27] evaluated IQ metrics for perceived sharpness of projection displays, where the images were blurred, and found that SSIM, FSIM and VIF produced good results.…”
Section: ) Full Reference Metricsmentioning
confidence: 99%